Computer Modeling of Second-Order Recursive Digital Filters of the Automated Design Signaling System - Novosyadly, S. P.; Valter, R. V. (Physics and Chemistry of Solid State, 2017)
In the article the analytical method of modeling software recursive digital filters of the second order with zeros on the circle of the single radius is presented. The corresponding algorithm of scaling of this composition of filters for signal CAD is developed.